O orfeonismo: oportunidade para um encontro imediato entre a arquivística e a musicologia? - Terra, Ana Lúcia (2017)
This text propose and discuss the contribution that archival science, rooted in a perspective of trans and interdisciplinary Information Science, can bring to the organization of collections related to musical activity, with its inventory, organization, preservation and promotion of access. The speciﬁc case of “orfeões” will be addressed from the perspective of a complex information system. We present a case study regarding the organization of the Orfeão Poveiro archival fund, from Póvoa de Varzim, using ICA-AtoM tool, an open source application that uses the international standards of archival description.